Nursing communication strategies with terminal lung cancer patients: A literature review (Research, Society and Development, 2025)
Introduction: Lung cancer is a neoplasm characterized by the uncontrolled growth of cells in the lungs, which can form malignant tumors and spread to other parts of the body. The communication of the nursing team plays an essential role and must be clear, empathetic, and respectful, addressing the emotional and psychological needs of the patient, ensuring humane, dignified, and compassionate care focused on relieving suffering. Objective: To analyze the main communication strategies used by nursing professionals with terminal patients diagnosed with lung cancer, considering the importance of this practice within the context of palliative care and the implications that inadequate communication may have on the patient’s quality of life. Methodology: This is a qualitative bibliographic review aimed at analyzing scientific publications on the impact of palliative care on the quality of life of patients with lung cancer.Results: Based on the findings, the study seeks to promote communication through active listening, welcoming, and dialogue. It aims to improve the quality of life of terminal patients through strategies adapted to the individual needs of each patient.Conclusion: The knowledge and effectiveness demonstrated in this study showed that the actions performed by nurses align with institutional guidelines on palliative care, such as implementing comfort measures, pain relief, psychological support, and therapeutic communication that fosters a bond between professionals, family, and patient.